Minding the markets : an emotional finance view of financial instability - Tuckett, David (Palgrave Macmillan, 2011)
"In this groundbreaking book, Tuckett argues that most economists' explanations of the financial crisis miss its essence; they ignore critical components of human psychology. He offers a deeper understanding of financial market behavior and investment processes by recognising the role played by unconscious needs and fears in all investment activity"--